Candida albicans aspartyl protease (Sap6) inhibits neutrophil function via a “Trojan horse” mechanism - Marcin Zawrotniak; Dorota Satala; Magdalena Juszczak; Grażyna Bras; Maria Rapala-Kozik (Scientific Reports)
Abstract Candida albicans, a prevalent fungal pathogen, employs aspartyl proteases such as Sap6 to evade immune defenses, challenging our understanding of host‒pathogen interactions. This research examined the impact of Sap6 on neutrophil responses, which are crucial for innate immunity. Employing flow cytometry and fluorescence microscopy, we explored how Sap6 affects neutrophil functions, particularly by focusing on reactive oxygen species (ROS) production, neutrophil extracellular traps release (NETosis), and apoptosis. Our findings revealed Sap6’s unique ability to bind and internalize in neutrophils, significantly attenuating ROS production through proteolytic damage to NADPH oxidase, resulting in blocking the ROS-dependent NETosis pathway. This disruption in neutrophil functions by Sap6 suggested the presence of a ‘Trojan horse’ mechanism by C. albicans. This mechanism reveals a sophisticated immune evasion strategy, shedding light on fungal pathogenicity and host immune interactions. Understanding fungal proteases in immune modulation could inspire new therapeutic approaches for fungal infections.